2006
DOI: 10.1111/j.1461-9555.2006.00287.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential patterns of colonization of coarse woody debris by Ips pini (Say) (Coleoptera: Scolytidae) following a major ice storm in Ontario

Abstract: 1 It is widely known that many bark and wood-boring beetle species use nonresistant coarse woody debris (CWD) created by disturbances; however, the ability of these secondary species to cause mortality in healthy trees following a build-up of their populations remains unclear. We characterized the pattern of colonization by Ips pini (Say) following a major ice storm that created large amounts of CWD varying in resistance to colonization (i.e. ranging from snapped tops with no resistance to heavily damaged tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…Possible reasons for the decline of early-successional subcortical insect flight activity with time are: increasing populations of insect (Ryall 2003;Ryall et al 2006) and avian (Baldwin 1968;Fayt et al 2005) natural enemies (Ryall and Smith 2001); greater inter-and intra-specific competition (Robins and Reid 1997); lower availability and quality of CWD as habitat on the disturbed landscape (Wallace 1953;Wickman 1965;Jacobs 2004); and/or rapid salvaging of other downed material on the landscape (USDA Forest Service 1962. Similar results were reported for the activity of I. pini in ice-damaged P. resinosa stands in Ontario where beetle activity declined markedly 2-4 years after the storm (Ryall et al 2006), and for the activity of Dendroctonus brevicomis LeConte in wind-damaged stands in California where beetle activity declined 2 years after the storm (Miller 1928). Populations of Ips typographus (L.) and other subcortical beetles peaked 2 years after a wind storm (Vivian) in Switzerland (Wermelinger et al 1999) and after another wind storm (Lothar) in 1999 in France (Nageleisen 2001).…”
Section: Subcortical Insect Species Compositionmentioning
confidence: 99%
“…Possible reasons for the decline of early-successional subcortical insect flight activity with time are: increasing populations of insect (Ryall 2003;Ryall et al 2006) and avian (Baldwin 1968;Fayt et al 2005) natural enemies (Ryall and Smith 2001); greater inter-and intra-specific competition (Robins and Reid 1997); lower availability and quality of CWD as habitat on the disturbed landscape (Wallace 1953;Wickman 1965;Jacobs 2004); and/or rapid salvaging of other downed material on the landscape (USDA Forest Service 1962. Similar results were reported for the activity of I. pini in ice-damaged P. resinosa stands in Ontario where beetle activity declined markedly 2-4 years after the storm (Ryall et al 2006), and for the activity of Dendroctonus brevicomis LeConte in wind-damaged stands in California where beetle activity declined 2 years after the storm (Miller 1928). Populations of Ips typographus (L.) and other subcortical beetles peaked 2 years after a wind storm (Vivian) in Switzerland (Wermelinger et al 1999) and after another wind storm (Lothar) in 1999 in France (Nageleisen 2001).…”
Section: Subcortical Insect Species Compositionmentioning
confidence: 99%
“…Large quantities of woody debris are deposited periodically on the forest floor during severe storms (see for example Keller et al, 2004;Ryall et al, 2006;Woodall and Nagel, 2007). The effect of severe storms on forests was noted in an investigation initiated following cyclone Bernie, in April 1982, when it was concluded that they have had a major influence on stand structure and pattern in indigenous forests throughout New Zealand (Shaw, 1983).…”
Section: Introductionmentioning
confidence: 96%
“…Trees were baited with ipsdienol and lanierone, both aggregation pheromones used by I. pini during host colonization [49]. This beetle has been reported to occasionally kill living trees [50][51][52] but generally behaves as a secondary species in eastern North American forests [53,54]. Mass attack by Ips pini and inoculation of its associated fungi into trees was likely responsible for ultimately killing trees.…”
Section: Discussionmentioning
confidence: 99%